Types of Question and Questioning Tactics Used by The Teacher of Children 3A Class - Chelinedyon Tella (Institute of Research and Community Outreach - Petra Christian University, 2018)
Questioning is one of the most important classroom activities. This study is conducted to find out the/ types of question and questioning tactics used by the teacher of Children 3A class at Petra Language Center (PLC). The theory used was from Wragg and Brown (2001). The data were all the questions asked by the teacher during the class meetings related to the lesson taken from two meetings, each lasted in 60 minutes. I used classroom observation as the instrument to collect my data. From the study, out of the three common types of questions, I found out that only two types of questions were used, i.e conceptual and empirical question. Meanwhile, only six questioning tactics were used, i.e structuring, directing and distributing, pitching and putting clearly, pausing and pacing, listening to replies and responding and sequencing. I concluded that the teacher of Children 3A class asked different types of question and used various questioning tactics to check students understanding by asking the meanings and definitions since students are in the beginner level, thus giving equal opportunities to every students to answer questions.